RANCANG BANGUN RANGKA MESIN PENGADUK DODOL KAPASITAS 10 KG - Ramdani, Rizki; Prayoga, Kiki; Saleh, Agus; Ginting, Edison; Apnena, Riri Damayanti; -, Wachidin (UPPM Politeknik TEDC Bandung, 2024)
Dodol is a traditional Indonesian food made from glutinous rice, palm sugar, coconut milk, salt, and water. All the ingredients are mixed and stirred until reaching a certain thickness, usually requiring 4-8 hours of cooking time. During the mixing process, dodol must be continuously stirred to prevent it from burning or forming a crust. This design aims to create a machine that can assist in the dodol production process, particularly in the stirring process, to make it more effective and efficient. The method involves designing a dodol stirrer machine frame. The design of this dodol stirrer machine frame uses Autodesk Inventor Professional 2023, with a material of 4x4 cm angle iron with a thickness of 3 mm, capable of supporting a load of 10 kg. The stress analysis results for this dodol stirrer frame are sufficiently safe, with a value of 29.5 MPa, compared to the maximum limit of 147.3 MPa. The results from the frame manufacturing process, using welding with an SMAW machine and E6013 electrodes, show that the frame can support each component and does not experience excessive vibration when the dodol stirrer machine is operational.